Biocompatible implant mimicking cartilage: A new horizon for reconstructive facial field. Issue 11 (27th June 2020) - Biswas, Biswajit Kumar; Dey, Sutapa; Chakrabarty, Anindya; Laha, Arghya; Mandal, Tapan Kumar; Karmakar, Laxmikanta; Das, Debajyoti
Abstract: Cartilage is avascular with limited to no regenerative capacity, so its loss could be a challenge for reconstructive surgery. Current treatment options for damaged cartilage are also limited. In this aspect there is a tremendous need to develop an ideal cartilage‐mimicking biomaterial that could repair maxillofacial defects. Considering this fact in this study we have prepared twelve silicone‐based materials (using Silicone 40, 60, and 80) reinforced with hydroxyapatite, tri‐calcium phosphate, and titanium dioxide which itself has proven their efficacy in several studies and able to complement the shortcomings of using silicones. Among the mechanical properties (Young's modulus, tensile strength, percent elongation, and hardness), hardness of Silicone‐40 showed similarities with goat ear ( P  > .05). Silicone peaks have been detected in FTIR. Both AFM morphology and SEM images of the samples confirmed more roughed surfaces. All the materials were nonhemolytic in hemocompatibility tests, but among the twelve materials S2, S3, S5, and S6 showed the least hemolysis. For all tested bacterial strains, adherence was lower on each material than that grown on the plain industrial silicone material which was used as a positive control. S2, S3, S5, and S6 samples were selected as the best based on mechanical characterizations, surface characterizations, in vitro hemocompatibility tests and bacterial adherence activity. So, outcomes of this present study would be promising when developing ideal cartilage‐mimicking biocomposites and their emerging applications to treat maxillofacial defects due to cartilage damage.